Optimization of monitoring of contractile uterus activity and fetus status in women with the threat of preterm birth - S.V. Korovai; I.V. Lakhno; O.V. Gryshchenko; K.V. Drogovoz; Y.S. Blazhko; A.S. Lutskyi (Publishing House TRILIST, 2021)
Research objective: to study the use of uterine activity and variables of acceleration capacity (AC) and deceleration capacity (DC) in uterine contractile activity and fetal well-being monitoring in women at risk of preterm birth. Materials and methods. 292 pregnant women were included in the prospective study. All involved women underwent ultrasound cervicometry at 16 weeks. 124 pregnant women with a "short cervix" of the III (main) group were observed in the dynamics, as well as uterine activity and fetal AC/DC at 26, 32 and 38 weeks of gestation, and during labor were studied. In 112 women of group II the variables of fetal AC/DC were detected at these terms of pregnancy. They were monitored via conventional cardiotocography during labor. 56 pregnant women in group I with normal cervicometry were monitored. Results. Sensitivity and specificity of the diagnosis of the threatened preterm birth in the main group was 97.30% and 94.74% respectively. Diagnostic accuracy in the case of uterine activity according to fetal non-invasive electrocardiography was 96.18%. Sensitivity and specificity of the diagnosis of the threatened preterm birth in the comparison group were significantly lower: 89.29% and 87.80% respectively. The diagnostic accuracy was 88.41%. Patients in all clinical groups at 26 weeks had low AC/DC values. However, later in women of group I was found highest AC/DC level. AC/DC values in patients with risk of preterm birth were reduced compared with controls (p < 0.05). Sensitivity and specificity of the diagnosis of fetal distress if AC/DC was used were 91.67% and 99.12% respectively. Diagnostic accuracy of the test was 98.41%. In the comparison group the sensitivity was 77.78%, and the specificity was 89.22%. Diagnostic accuracy of intranatal cardiotocography was 86.82%. Conclusions. Uterine activity extracted from the maternal abdominal signal can significantly improve the diagnosis of the threatenedpreterm delivery. Patients at risk of preterm birth have a delayed fetal neurological, which leads to fetal distress. AC/DC variables obtained via fetal non-invasive electrocardiography allow increasing the accuracy of fetal distress diagnosis.